Diversity of Enchytraeidae (Annelida: Clitellata) in habitats within the Magnesian Limestone Plateau of County Durham, U.K. - Valerie Standen; Ulfert Graefe; Rüdiger M. Schmelz; Jiří Schlaghamerský (Soil Organisms, 2009)
Sampling of various terrestrial habitats (woodland, grassland, sea edge) of Hawthorn Dene and surroundings within the Magnesian Limestone plateau of County Durham yielded 17 species of Enchytraeidae and the naidid/tubificid Rhyacodrilus falciformis. Five enchytraeid species were recorded for the first time in the British Isles: Fridericia auritoides, F. maculatiformis, F. semisetosa, F. sylvatica, and F. isseli.